Identification of a small molecule 1,4-bis-[4-(3-phenoxy-propoxy)-but-2-ynyl]-piperazine as a novel inhibitor of the transcription factor p53 - Liu Xin; Zhang Ying; Tong Man; Liu Xiu-ying; Luo Guan-zheng; Xie Dong-fang; Ren Shao-fang; Bai Dong-hui; Wang Liu; Zhou Qi; Wang Xiu-jie (Acta Pharmacologica Sinica, 2016)
Xin LIU1, #, Ying ZHANG2, #, Man TONG1, Xiu-ying LIU1, 3, Guan-zheng LUO1, Dong-fang XIE1, Shao-fang REN1, Dong-hui BAI2, 3, Liu WANG2, Qi ZHOU2, Xiu-jie WANG1, * 1Center for Molecular Systems Biology, Institute of Genetics and Developmental Biology, Chinese Academy of Sciences, Beijing 100101, China; 2State Key Laboratory of Reproductive Biology, Institute of Zoology, Chinese Academy of Sciences, Beijing 100101, China; 3University of Chinese Academy of Sciences, Beijing 100049, China Aim: To identify novel small compound inhibitor of p53 protein. Methods: Mouse embryonic fibroblasts (MEF) and mouse embryonic stem (ES) cells were tested. Cell proliferation rate was determined using a Cell Proliferation Kit. The mRNA and protein levels of p53-related genes were measured using real-time PCR and Western blotting, respectively. Global response in the p53 signaling network was analyzed using Illumina whole-genome expression BeadChips. Results: Treatment of MEF cells with a small molecule 1,4-bis-[4-(3-phenoxy-propoxy)-but-2-ynyl]-piperazine (G5) at 10 µmol/L for 24 h markedly reduced the mRNA and protein levels of the p53 downstream genes MDM2 and p21. In G5-treated ES cells, a total of 372 differentially expressed genes were identified, and 18 among them were direct downstream genes of p53; 6 out of 9 p53-repressed genes were upregulated, and 5 out of 9 p53-activated genes were downregulated. In both MEF cells and ES cells, treatment of with G5 (10 µmol/L) up to 48 h neither affected the proliferation rate nor caused morphological alterations. Conclusion: G5 inhibits p53 activity and simultaneously preserves the normal growth and proliferation of cells, therefore is a new compound for studies of p53-mediated cell manipulation. Keywords: 1,4-bis-[4-(3-phenoxy-propoxy)-but-2-ynyl]-piperazine; tumor suppressor protein; p53; p53 inhibitor; embryonic fibroblast; embryonic stem cell; proliferation This study was supported by grants from the “Strategic Priority Research Program” of the Chinese Academy of Sciences (Grant No XDA01020105), the 973 program of China (2011CBA01101) and the 863 program of China (2011AA020108). # These authors contributed equally to this work. * To whom correspondence should be addressed. E-mail xjwang@genetics.ac.cn Received 2013-01-22 Accepted 2013-05-02